Approaching Trash: An Autonomous IoT Mobile Bin for Nudging Waste Disposal Habits in Smart Environments (Architecture Image Studies, 2025)
The problem of littering persists to the present day, and conventional static trash cans often fail to encourage proper waste disposal. This study proposes a mobile, IoT-enabled trash bin that approaches users rather than requiring users to approach it. The prototype integrates Raspberry Pi 4 as the central controller, L298N motor drivers for movement, an ultrasonic sensor to detect obstacles, and an infrared sensor to identify users who wish to dispose of waste, enabling the lid to open and close automatically. Through a web-based interface built with Flask and Nginx, the system can record and replay movement trajectories on demand, allowing the bin to follow predefined paths autonomously. Usability testing with 20 respondents produced a mean System Usability Scale (SUS) score of 69.125, indicating that the prototype achieves an acceptable level of usability and interaction. These results suggest that the IoT-based mobile trash bin has the potential to support the development of proper waste disposal habits while demonstrating a practical and educational application of IoT in waste management.